SYSTEMIC LUPUS ERYTHEMATOSUS AND RENAL LESIONS: CLINICOPATHOGENETIC ASPECTS (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
Systemic lupus erythematosus (SLE) is a multifactorial disease caused by a complex interaction of genetic and exogenous factors underlying multiple disorders of innate and acquired immunity, including hyperproduction of cytokines, pathological activation of B cells, disturbances in intracellular signaling of T cells, and clearance defects. cells undergoing apoptosis and necrosis. The purpose of this review is to analyze recent literature data regarding the prevalence and pathogenetic mechanisms of the development of kidney damage (lupus nephritis) in SLE. Among human autoimmune diseases, SLE is predominantly prevalent among females (female to male ratio is approximately 10:1). The dependence of kidney damage on the degree of activity and course of SLE was noted. Most often, lupus nephritis occurs in acute and subacute SLE. Lupus nephritis develops in 55% of adult patients with SLE and 75% of children. The clinical picture of lupus nephritis, in most cases, is due to histological changes. Prognostically unfavorable clinical manifestations of lupus nephritis are nephrotic proteinuria, arterial hypertension, and a decrease in glomerular filtration rate for three months. Detection of subendothelial deposits, damage to more than 50% of the glomeruli, class IV lupus nephritis, including foci of fibrinoid necrosis and crescents, are considered predictors of deterioration in renal function.